Life cycle and behaviour of the predaceous mite Cunaxatricha tarsospinosa (Acari: Prostigmata: Cunaxidae) - de Castro, Tatiane M. M. G. [UNESP]; de Moraes, Gilberto J. (Springer, 2010)
Life cycle and behaviour of Cunaxatricha tarsospinosa Castro & Den Heyer from rubber trees in Brazil were studied, with Tenuipalpus heveae Baker offered as prey. The study was conducted at 25.4 +/- A 0.2A degrees C, 83 +/- A 5% RH and 12:12 h L:D photophase. The egg stage was the longest immature stage, lasting 17.1 +/- A 1.3 days (mean +/- A SE); total juvenile development was completed in 33.2 +/- A 2.8 days. Lifetime fecundity was 12.0 +/- A 2.2 eggs. Intrinsic rate of population increase was low, suggesting that T. heveae may not be a good prey for the predator. All specimens of C. tarsospinosa collected in the field for this study were females, no males were found. Concurrently, only females were obtained in the laboratory. This seems to be the first report of thelytokous parthenogenesis for cunaxids. Similar to earlier reports for some Cunaxinae and Coleoscirinae, prey were captured when predators were actively searching for them.
Keywords: Biology; Tenuipalpus heveae; Rubber tree; Predator; Thelytoky